Advances in spectroscopic monitoring of the atmosphere - Chen, Weidong; Venables, Dean S.; Sigrist, Markus W., 1948- (Elsevier, 2021)
Provides a comprehensive overview of cutting-edge technologies and monitoring applications. Concepts are illustrated by numerous examples with information on spectroscopic techniques and applications widely distributed throughout the text. This information is important for researchers to gain an overview of recent developments in the field and make informed selections among the most suitable techniques. This volume also provides information that will allow researchers to explore implementing and developing new diagnostic tools or new approaches for trace gas and aerosol sensing themselves. Advances in Spectroscopic Monitoring of the Atmosphere covers advanced and newly emerging spectroscopic techniques for optical metrology of gases and particles in the atmosphere. This book will be a valuable reference for atmospheric scientists, including those whose focus is applying the methods to atmospheric studies, and those who develop instrumentation. It will also serve as a useful introduction to researchers entering the field and provide relevant examples to researchers and students developing and applying optical sensors for a variety of other scientific, technical, and industrial uses. Key Features: Overview of new applications including remote sensing by UAV, laser heterodyne radiometry, dual comb spectroscopy, and more. Features in-situ observations and measurements for real-world data. Includes content on leading edge optical sensors.--Provided by publisher.